439. Ternary Expression Parser

Given a string representing arbitrarily nested ternary expressions, calculate the result of the expression. You can always assume that the given expression is valid and only consists of digits 0-9, ?, :, T and F (T and F represent True and False respectively).

Note:

  1. The length of the given string is ≤ 10000.
  2. Each number will contain only one digit.
  3. The conditional expressions group right-to-left (as usual in most languages).
  4. The condition will always be either T or F. That is, the condition will never be a digit.
  5. The result of the expression will always evaluate to either a digit 0-9, T or F.

Example 1:

Input: "T?2:3"

Output: "2"

Explanation: If true, then result is 2; otherwise result is 3.

Example 2:

Input: "F?1:T?4:5"

Output: "4"

Explanation: The conditional expressions group right-to-left. Using parenthesis, it is read/evaluated as:

             "(F ? 1 : (T ? 4 : 5))"                   "(F ? 1 : (T ? 4 : 5))"
          -> "(F ? 1 : 4)"                 or       -> "(T ? 4 : 5)"
          -> "4"                                    -> "4"

Example 3:

Input: "T?T?F:5:3"

Output: "F"

Explanation: The conditional expressions group right-to-left. Using parenthesis, it is read/evaluated as:

             "(T ? (T ? F : 5) : 3)"                   "(T ? (T ? F : 5) : 3)"
          -> "(T ? F : 3)"                 or       -> "(T ? F : 5)"
          -> "F"                                    -> "F"

Rust Solution

struct Solution;

impl Solution {
    fn parse_ternary(expression: String) -> String {
        let expression: Vec<char> = expression.chars().collect();
        Self::parse(&expression).iter().copied().collect()
    }

    fn parse(expression: &[char]) -> &[char] {
        let n = expression.len();
        if n == 1 {
            expression
        } else {
            let mut count = 1;
            for i in 2..n {
                if expression[i] == '?' {
                    count += 1;
                    continue;
                }
                if expression[i] == ':' {
                    count -= 1;
                    if count == 0 {
                        return if expression[0] == 'T' {
                            Self::parse(&expression[2..i])
                        } else {
                            Self::parse(&expression[i + 1..])
                        };
                    }
                }
            }
            &[]
        }
    }
}

#[test]
fn test() {
    let expression = "T?2:3".to_string();
    let res = "2".to_string();
    assert_eq!(Solution::parse_ternary(expression), res);
    let expression = "F?1:T?4:5".to_string();
    let res = "4".to_string();
    assert_eq!(Solution::parse_ternary(expression), res);
    let expression = "T?T?F:5:3".to_string();
    let res = "F".to_string();
    assert_eq!(Solution::parse_ternary(expression), res);
}

Having problems with this solution? Click here to submit an issue on github.